Sustainable collaborative supply networks in the international clothing industry: a comparative analysis of two retailers - MacCarthy, Bart L.; Jayarathne, P.G.S.A. (Taylor & Francis, 2012)
Collaborative supply networks in the international clothing industry are of major economic significance in many countries, particularly in developing economies. The sector has gone through substantial changes in the last decade with the abolition of trade barriers and the increasingly dominant position of major retailers and brand owners in supply networks. The sustainability of clothing supply networks is subject to increasing public scrutiny. In this work, the characteristics and operation of collaborative clothing supply networks have been analyzed. Two contrasting supply networks – one for a major leading brand retailer and one for a major supermarket retailer - are analyzed and compared from a sustainability perspective. The challenges in assessing economic, social and environmental aspects of sustainability at a network level are highlighted. The results show a minimum compliance culture in the supermarket supply network, whereas the leading brand retailer demonstrates a much higher level of proactive and positive sustainability practices and actions across the network. The study highlights the benefits of a strongly collaborative network in helping to facilitate and enhance a sustainability agenda. The implications of the study are discussed for retailers, manufacturers and policy makers, as well as for the governance of collaborative supply networks more generally.